Torsional behaviour of tapered CFDST members with large void ratio. (15th July 2022) - Fan, Jia-Hao; Wang, Wen-Da; Shi, Yan-Li; Ji, Sun-Hang
Abstract: This paper investigated the mechanical behaviour of tapered concrete-filled double skin steel tubular (CFDST) members under combined axial compression and torsion. A series of experiments on CFDST specimens were tested including 8 tapered members and 2 normal members with various hollow ratios and axial compression ratios. The torsional performance of tapered members was analyzed on failure modes, torque-rotation angle curves, and torque-shear strain curves. Verified FE models were developed to carry out the full-range analysis, stress and strain distribution, and the contact stresses between the components. The results showed that the failure mode of tapered CFDST columns was the torsional deformation occurred between 0.5 H and the top section. The specimens with a high axial compression ratio occurred additionally inclined outward buckling at 0.8 H section, giving rise to a decline in torsional capacity. A low level of axial force promotes the torsional bearing capacity. The effects of the taper angle and hollow ratio on the distribution of shear strain and the torsional capacity at different heights are obvious. Furthermore, employing the section with the lowest torsional modulus for tapered CFDST members is conservative as the designed section, because the torsional capacity might be underestimated. Finally, a simplified method defined by a new calculated section for forecasting the torsional performance of tapered CFDST members is proposed. Highlights: Torsion tests of tapered CFDST columns with void ratio of 0.7–0.8. The experiment and simulation of tapered CFDST members were investigated. The effect of hollow ratio and taper angle on shear strain was estimated. A simplified method for tapered CFDST torsion members was proposed.